Transcribing public libraries as revitalized ethical spaces. (October 2022) - Frayne, Alison
Referencing human rights and library literature, this article seeks to contribute to an understanding of how the IFLA Statement on Libraries and Intellectual Freedom is articulated by library associations and libraries, whose policies are structured by institutional mandates that determine library function. The article re-envisages intellectual freedom premised on a collective identity of fairness, justice and equality. Drawing on the IFLA Statement, the Universal Declaration of Human Rights and the United Nations Declaration on the Rights of Indigenous Peoples, this article uses a rhetorical analysis methodology to discuss the re-envisioning of library functionality in contemporary society. Public libraries are unique public institutions that carry people's stories in the literatures and knowledges they hold. They open the way for everyone to engage actively with ethical statements that reflect a collective of voices, where intellectual freedoms extend the narrative of collective memories.